Photoluminescence characteristic of magnesium Boro-Tellurite doped Eu3+ Ceramic - Nur Zu Ira Bohari,; R. Hussin,; Zuhairi Ibrahim,; Hendrik O. Lintang, (Universiti Kebangsaan Malaysia, 2015)
The series samples of xTeO2-(70-x)B2O3-30MgO with 0≤x≤30 mol% have been prepared via the solid-state reaction method. The composition sample of 30TeO2-40B2O3-30MgO were chosen as a doped sample in the composition of 100-y(30TeO2-40B2O3-30MgO)-yEu3+ with 0.2≤y≤2 mol% and were heated at 750oC. The XRD results showed that the major phase was Mg(Te2O5) while MgO(B2O3)2, MgTe6O13, Mg2(B2O5) and MgB4O7 was observed as a minor phase. The small phase of EuB2O4 and Eu2Te4O11 were detected by XRD when the composition of 30TeO2-40B2O3-30MgO were doped with 1.5% of Eu3+. The EDX analysis of 30TeO2-40B2O3-30MgO doped with 1.5% Eu3+ sample was confirmed the presence of boron (B), magnesium (Mg), tellurium (Te), oxygen (O) and europium (Eu) elements. From the FESEM images, the surface morphology of doped 1.5% Eu3+ samples was agglomerated compared with the undoped sample. The average diameter of the grain size is in the range of 50-100 μm. The emission spectra of the Eu3+-doped 30TeO2-40B2O3-30MgO ceramic consists of intense and sharp lines ranging from 550-725 nm. The luminescence spectra showed that the emission intensity of 30TeO2-40B2O3-30MgO doped with Eu3+ was enhanced with the increase of Eu3+ ion from 0.2 to 1.5 mol%, which resulted in enhancement of the red emission of the samples. The longest decay time for 30TeO2-40B2O3-30MgO doped with 1.5 mol % Eu3+ was 0.892 ms.